Utilizing network pharmacology and experimental validation to investigate the underlying mechanism of phellodendrine on inflammation - Lili Hu; Jue Wang; Na Wu; Xiaoge Zhao; Donghui Cai (PeerJ, 2022)
Background Phellodendrine, one of the characteristic and important active components of Cortex phellodendri, has been proven to show anti-inflammatory effects. However, the underlying mechanism of phellodendrine on inflammation remains largely unclear. Aim of the study In this study, network pharmacology and experimental validation were used to explore the underlying mechanism of phellodendrine on inflammation. Materials and Methods PubChem and SwissADME database were used to evaluate the drug-likeness and other characteristics of phellodendrine. The targets of phellodendrine for the treatment of inflammation were analyzed with multiple databases. Other extensive analyses including protein–protein interaction, Gene Ontology, and Kyoto Encyclopedia of Genes and Genomes pathway enrichment were accomplished with the STRING database, Cytoscape software, and DAVID database. Moreover, the effect of phellodendrine on anti-inflammation was proven in RAW264.7. Results The network pharmacology results indicated that phellodendrine had drug potential. Phellodendrine acted directly on 12 targets, including PTGS1, PTGS2, HTR1A, and PIK3CA, and then regulated cAMP, estrogen, TNF, serotonergic synapse, and other signaling pathways to exert anti-inflammatory effects. The experimental results showed that phellodendrine reduced the levels of IL-6 compared with the LPS group in 24 h and changed the mRNA expression of PTGS1, PTGS2, HSP90ab1, AKT1, HTR1A, PI3CA, and F10. Conclusion Our research preliminarily uncovered the therapeutic mechanisms of phellodendrine on inflammation with multiple targets and pathways. Phellodendrine may be a potential treatment for inflammation-related diseases related to the cAMP and TNF signaling pathways.